Remote sensing and image interpretation - Lillesand, Thomas M.; Kiefer, Ralph W.; Chipman, Jonathan W.
From recent developments in digital image processing to the next generation of satellite systems, the sixth edition of this comprehensive text introduces students to the latest developments in the exciting field of remote sensing and image interpretation. The text examines the basics of analog image analysis while placing greater emphasis on digitally based systems and analysis techniques. The presentation is discipline neutral, so students in any field of study can gain a clear understanding of these systems and their virtually unlimited applications